DETERMINATION OF FACTORS AFFECTING MEDICATION ADHERENCE IN TYPE 2 DIABETES MELLITUS PATIENTS IN A TERTIARY HOSPITAL: CASE-CONTROL STUDY - WAHYUNI, ARIFAH S.; MARWA, DEWANTI; OKTASARI, SHOLIKHAH R.; YULIANTI, TRI; NUGRAHENI, AMBAR Y.; AL-SAMEA, RAMEZ A. M. O. (International Journal of Applied Pharmaceutics, 2025)
Objective: Several variables can impact medication adherence. Patients with type 2 diabetes mellitus (T2DM) still have low medication adherence, which increases their risk of hospitalization, uncontrolled blood sugar levels, and consequences from other illnesses. The study aimed to identify variables associated with medication adherence in T2DM outpatients to define a pharmacist intervention model or digital adherence technologies developed to improve medication adherence. Methods: A case-control study was conducted on a sample of 100 respondents. A census was conducted on all outpatients of T2DM at the Tertiary Hospital in Central Java, Indonesia, from June 1st to July 31st 2024 to select cases and control groups after out and completing the questionnaire. The medication adherence questionnaire used in this study is a self-developed questionnaire by the researcher, which has been tested for validity (r>0.361) and reliability (0.737). Adherence was analyzed descriptively, where a score of 9 indicated adherence. Bivariable and multivariable logistic regression was used to evaluate adherence factors. Results: The respondent’s adherence to medication was 60% as measured by the Medication adherence questionnaire for T2DM. Occupation, health insurance, number of DM medications, duration of therapy, comorbidities, gender, age, and family support had no significant effect on patient adherence (p>0.05). Factor significantly associated with medication adherence were education level (OR = 2.513, p = 0.028). Conclusion: Education can influence patient medication adherence. Pharmacists can actively contribute by providing education and counseling to improve patients’ understanding of their disease and enhance medication adherence.